SYSTEMATIC LITERATUR REVIEW: MEDIA PENANAMAN KARAKTER GEMAR MEMBACA BAGI SISWA SD - rani setiawaty; Nasywa Sabilarrahmah; Aat Alivia Nur Yasin; Vina Lailatul Oktaviani; Nila Amalia Nabila (Alifbata : Jurnal Pendidikan Dasar, 2025)
Reading is a very important skill to support children's academic success and character development. However, interest in reading among elementary school students in Indonesia is still relatively low. This research aims to explain the media used to instill the character of a love of reading. The method used is Systemtic Literature Review (SLR) by analyzing 21 related journals. Data was collected through the Google Scholar Database with the keywords "Media", "Characters Who Like Reading", "Primary School Students" and "Literacy". The results of this research show that media such as illustrated books, Big Books, Game Modules, Folk Stories and Digital Media have an effective role in building the habit of reading. Each media has interesting advantages and can be adapted to the age and learning context of students. Success in instilling the character of a love of reading can be supported by teachers, parents and the school environment. This research states that choosing the right media and consistent application to create a strong literacy culture in the elementary school education environment.